Improving literacy competence for junior high school teachers - Brillianing Pratiwi; Arini Noor Izzati; Ratu Badriyah; Ulfa Mariana (Community Empowerment, 2022)
During discussions with the teachers at Said Na'um Islamic Junior High School, it was discovered that there were issues with the school's facilities and infrastructure, specifically the lack of printed learning resources as enrichment materials for students. Therefore, it was agreed on priorities for teacher problem solving efforts in improving information literacy competence, so that they are able to utilize technology-based information. The implementation of this service involves several steps, including observation, implementation, and program evaluation. The implementation of the training on digital literacy skills will be held in September 2021. The results of the activity show a good response from teachers where 85% actively attend the program, 50% of them submitted the task and have been able to use digital technology well. As for 80% of the participants have mastered the ability to browse the literature.